Un tournant dans l’imaginaire ruiniste ? De la ruine littéraire dix-neuviémiste comme matériau d’avenir - Laure Lévêque (Babel: Littératures Plurielles)
Eversince Roland Mortier’s masterpiece Poetics of Ruins in France (1974), everybody has been aware of the importance this motif has assumed in the way we imagine time and how we experience it. Even to the point of creating fake ruins from bits and ends in the famous park follies that flourished in the 18th century, that would underpin meditations on fate. While this eschatological perspective broadly dominates Volney’s Ruins; or Meditations on the Revolutions of Empires (1791) where memento mori echoes from Nineveh to Palmyra, Tyre, Persepolis or Baalbek, a new poetics of the ruins seems to be coming forth, ushering in an archaeology of the future. These are the attributes investigated here in the works of Alexandre Dumas, Alfred Bonnardot and Albert Robida.